Journal Open Access and Plan S: Solving Problems or Shifting Burdens?. Issue 3 (29th January 2021) - Kamerlin, Shina Caroline Lynn; Allen, David J.; de Bruin, Bas; Derat, Etienne; Urdal, Henrik
ABSTRACT: This academic thought piece provides an overview of the history of, and current trends in, publishing practices in the scientific fields known to the authors (chemical sciences, social sciences and humanities), as well as a discussion of how open access mandates such as Plan S from cOAlition S will affect these practices. It begins by summarizing the evolution of scientific publishing, in particular how it was shaped by the learned societies, and highlights how important quality assurance and scientific management mechanisms are being challenged by the recent introduction of ever more stringent open access mandates. The authors then discuss the various reactions of the researcher community to the introduction of Plan S, and elucidate a number of concerns: that it will push researchers towards a pay‐to‐publish system which will inevitably create new divisions between those who can afford to get their research published and those who cannot; that it will disrupt collaboration between researchers on the different sides of cOAlition S funding; and that it will have an impact on academic freedom of research and publishing. The authors analyse the dissemination of, and responses to, an open letter distributed and signed in reaction to the introduction of Plan S, before concluding with some thoughts on the potential for evolution of open access in scientific publishing.